1997
DOI: 10.1055/s-2006-957598
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Relaxing Flavonoids and Terpenoids fromConyza filaginoides*

Abstract: Activity-guided fractionation of the smooth muscle relaxing, chloroform-methanol (1:1) extract of Conyza filaginoides (D.C.) Hieron (Asteraceae) led to the isolation of three flavonoids (quercetin 3-glucoside, rutin, and pinostrobin), one sterol (alpha-spinasterol), a sesquiterpenoid (beta-caryophyllene 4,5-alpha-oxide), and two triterpenoids (erythrodiol and 3-beta-tridecanoyloxy-28-hydroxyolean-12-ene). 3-beta-Tridecanoyloxy-28-hydroxy-olean-12-ene is a new naturally occurring terpenoid. All the isolated com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 6 publications
0
34
0
2
Order By: Relevance
“…Therefore, α-spinasterol strongly contributed to the antinociceptive effect of P. sabulosa HE. The proposed mechanism of action likely involves a disruption on glutamatergic pathways and calcium movement [9,34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, α-spinasterol strongly contributed to the antinociceptive effect of P. sabulosa HE. The proposed mechanism of action likely involves a disruption on glutamatergic pathways and calcium movement [9,34].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific investigations using different pharmacological tests are performed to prove their potential efficiency. That used the evaluation of antispasmodic activity on some isolated organs have demonstrated that some of these medicinal plant species possess significant and interesting spasmolytic (Mata et al, 1997;Trute et al, 1997;Sadraei et al, 2003;Cortés et al, 2006;Cechinel-Filho et al, 2007) or spasmogenic (Gilani et al, 2005(Gilani et al, , 2007 activity. In some cases, mechanisms underling the antispasmodic activity of tested extracts are also reported (Gilani et al, 2005(Gilani et al, , 2006(Gilani et al, , 2007(Gilani et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are well known for their spasmolytic activity (Williamson et al, 1998). Most spasmolytic flavonoids in the literature contain a flavone (Hazekamp et al, 2001), flavonol (Bergendorff and Sterner, 1995), isoflavone and flavanone skeleton (Rojas et al, 1996;Mata et al, 1997). The flavonoids isolated from S. samarangense have a chalcone and flavanone skeleton.…”
Section: Introductionmentioning
confidence: 99%